Variasi Bahasa dalam Iklan Situs Belanja Online (Shopee) - Lutfi Anjarwati; atiqa sabardila (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2022)
Language variations are part of the variety of languages ​​which are used in functions and situations, of course with the applicable language rules. This study aims to describe variations in slang and foreign language variations in online shopping site advertisements (Shopee). The method used in this research is descriptive qualitative. The data source used is the Shopee application, with data in the form of foreign language words and slang. The method of data collection is a documentation study with reading and note-taking techniques. The data analysis technique uses data triangulation. The results of the study found two forms of language variation, namely the form of foreign language variations and the form of slang. The research found 31 data with 11 variations of slang and 20 variations of foreign languages. The dominant foreign language variation is the use of English, where English is a language that can be used by everyone around the world. Meanwhile, variations in slang have a combination of two words combined into a word that is easier to pronounce, especially when it is often used among teenagers, as well as the omission of vowels from the word. The use of slang is a strategy on the part of Shopee to be able to easily convey messages to buyers by following current trends.